Molecular study of Rasd1 transcriptional regulation and Rasd1-NonO interaction. - Ong, Angeline Shufen. (2013)
RAS, Dexamethasone-induced 1 (Rasd1) is a monomeric guanosine 5’-triphosphate (GTP) binding protein of the Ras subfamily involved in diverse physiological roles including circadian rhythm, stress and iron homeostasis. In this study, transcriptional regulation of Rasd1 and identification of novel interacting partner of Rasd1 are investigated to better understand how Rasd1 performs these physiological functions. The Rasd1 minimal promoter is identified to reside within 111 bp upstream of Rasd1 via study of the Rasd1/luciferase fusion constructs. Subsequent studies using site-directed mutagenesis, reporter gene fusion assays, gene knockdown, chromatin immunoprecipitation (ChIP) and Real-Time (RT-PCR) experiments show that transactivators, D site of albumin promoter binding protein (Dbp; transcription factor involved in the output pathway of circadian rhythm) and glucocorticoid receptor (GR; transactivates Rasd1 upon Dexamethasone (Dex; synthetic glucocorticoid) induce Rasd1 promoter activity. I also find that Dbp enhances Rasd1 promoter activity by binding to the CCAAT/enhancer binding protein beta (C/EBPβ) site located at the 5’ untranslated region (UTR) of Rasd1. Circadian expression of Rasd1 requires promoter sequence of Rasd1 and downstream GRE elements and is modulated by Dbp. In addition, my studies identify NonO, Non-POU domain-containing octamer-binding protein, as a novel Rasd1 interacting partner, which is involved in regulation of cyclic adenosine monophosphate (cAMP) pathway, circadian rhythm, RNA processing and transcription. Interaction of Rasd1 and NonO is validated with affinity pulldowns, co-IP assays and indirect immunofluorescence. Investigation via reporter gene assays, ChIP and gene knockdown suggest that Rasd1 modulates NonO to function as a co-repressor of the cAMP pathway by interacting at the cAMP response element (CRE) site of specific target genes – nuclear orphan receptor 4A (NR4A) 1 and 2. The GTP hydrolysis activity of Rasd1 is required for the functional interaction. These findings reveal a novel mechanism by which the coregulator activity of NonO can be modulated.